Cognitive disorder and associated factors among pregnant women attending antenatal service at Dilla University Referral Hospital, 2022 - Kassaw, Chalachew; Wale, Tiruwork; Negash, Misrak; Temesgen, Kiber; Mekuriaw, Birhanie; Tolessa, Omega; Abdisa, Elias Nigusu; Chekol, Yigrem Ali; Ayano, Getinet; Anbesaw, Tamrat (Frontiers in Global Women's Health, 2023)
Introduction Cognition is defined as the mental activity or process of learning information and understanding through reason, experience, and the senses. In Sub-Saharan African nations like Ethiopia, such assessments of a pregnant mother's mental health during antenatal care are uncommon procedures. Instead, there is a greater focus on the physical well-being of the woman and her fetus. As a result, this study aimed to evaluate the cognitive deficits and related factors in a pregnant women attending an antenatal care service. Methods This hospital-based cross-sectional study included 415 pregnant women who were receiving antenatal care at Dilla University Referral Hospital in Dilla, Gedeo Zone, Ethiopia. In this study, respondents were chosen using systematic random sampling, and study participants were interviewed using administered questions to gather pertinent data. This study used the OSLO Social Support Scale, the Alcohol, Smoking, and Substance Involvement Screening Test, and the Mini-Mental Status Examination to assess the social support, cognitive status, and current substance use history of a respondent. Descriptive statistics including frequencies, graphs, and percentages were used to describe the results. A logistic regression analysis was conducted to determine the connection between independent factors and the outcome variable at a 95 percent confidence level and p < 0.05. Result Among all respondents who came for antenatal care visits, only 24 (5.8%) were unmarried (single, divorced, widowed). The mean age of respondents was 26 years old and 155 (37.3%) had attended secondary school. Variables such as strong social support [0.11 (0.03–0.23), p < 0.02], being a follower of orthodox religion [0.24 (0.12–0.39), p < 0.04], ≥5,000 Ethiopian birr monthly income [0.28 (0.17–0.48), p < 0.02], age >26 years old [1.23 (1.14–2.54), p < 0.04], unplanned pregnancy [2.78 (1.45–4.32), p < 0.02], and rural residence [3.90 (2.23–7.34), p < 0.04] were significantly associated with cognitive impairment at 95% confidence interval and a p-value <0.05. Conclusion This study found that pregnant women who attended antenatal care experienced a significant reduction in cognitive disorders. Additionally, this study revealed adjustable factors such as unwanted pregnancy, social support, and religiosity. It is preferable to check a pregnant woman's cognitive condition at antenatal services and to follow-up on each additional visit.